Relationship of venom ontogeny and diet in Bothrops - Andrade, Denis V. [UNESP]; Abe, Augusto Shinya [UNESP] (My University, 1999)
We studied ontogenetic changes in venom toxicity of the pitvipers Bothrops jararaca and B. alternatus in order to evaluate the relationship between venom action and diet. Toxicity tests (LD50) were performed for the venoms of adult and juvenile snakes on mice and bullfrog froglets, which represented endothermic and ectothermic prey respectively. The venom of juveniles of B. jararaca, but not of B. alternatus, had a higher toxicity on anurans than that of adults. This finding is consistent with the feeding habits of these two species, because juveniles of B. jararaca feed mainly on small anurans and lizards, shifting to endothermic prey at maturity, whereas B. alternatus preys mainly on endotherms throughout its life. Venom toxicity in endotherms was higher for adults of B. jararaca compared to juveniles, a feature not observed for B. alternatus. It is proposed that prey death/immobilization is the main function of the venom of juvenile snakes. As the snake grows, the digestive role of venom may become increasingly important, because adults prey upon large and bulky prey. The importance of adult venoms in prey digestion is reflected in their higher proteolytic activity.
Keywords: Bothrops; Electrophoresis; Venom ontogeny; Venom specificity; Viperidae; diet; ontogeny; snake; toxicity test; Bothrops alternatus; Bothrops jararaca